Wage Management of Logistics - Rukhayevsky, Dmitry; Pistunov, Ihor (LAP LAMBERT Academic Publishing, 2019)
The multivariable method of the specialists in logistics wage calculation in modern Ukrainian enterprises functioning under the conditions of the market economy meaning the formation of the mathematic model in which such factors as education, experience, psychological parameters are formalized is offered. The psychological factors of the logistic business activity are classified and, the most significant of them are specified, the psychological testing method which allows to both formalize the results of all corresponding factors and further use the received results while complex calculating the recommended level of the wage of the specialist in logistics is offered. The unique cross-correlation model of the specialists in logistics recommended level of salary calculation due to three groups of factors - the education, the experience, the psychological parameters is formed. This method includes the following stages: questionnaire capture of data; the psychological testing; the use of the received formalized results in the mathematic model of the specialists in logistics recommended level of salary calculation; the account of the inflationary factor.
Keywords: математичне моделювання; рівень заробітної плати фахівця; психологічне випробування; психологічні чинники ділової активності